(untitled) (Journal of Science Foundation, 2016)
An experiment was conducted at the Experimental Farm of the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur during November 2011 to May 2012 to determine the effect of pre-emergence herbicide Pretilachlor @ 75%, 100%, 125%, 150%, 175% and 200% of the recommended dose under two water management regime i.e. continuous flooding and field capacity on weed suppression and yield performance of Boro rice cv. BRRIdhan28. One weed free and one control (unweeded) treatment were also imposed for treatment comparison. The experiment was laid down in Split Plot design with three replications. Standard management practices for transplanted rice were followed. Continuous flooding was found to contribute better weed control efficiency than field capacity. At 60 DAT, the highest weed control efficiency of 65.75% was found in the treatment receiving Pretilachlor @ 125% of the recommended dose under continuous flooding and the least (54.76%) was found in the treatment receiving 75% of the recommended dose under field capacity. Continuous flooding contributed to more tillers than field capacity, and herbicide up to 125% of the recommended dose enhanced tillering in rice. At 75DAT the highest number of tillers (17.53 hill-1) were found in the plots receiving Pretilachlor @ 125% of the recommended dose under good water management (W1T3), while the lowest (11.10 hill-1) was recorded in W2T6 treatment receiving Pretilachlor @ 200% of the recommended dose under field capacity. The highest tiller mortality (27.90%) was observed in W1T3 treatment, whereas the least (8.06%) was observed in W2T5 treatment receiving the same herbicide @175% of the recommended dose under field capacity. Application of Pretilachlor at recommended dose under continuous flooding contributed to the highest crop dry matter production (1144.60g m-2) thus leading to the highest grain yield of 6.31 t ha-1 being followed by the treatment receiving Pretilachlor @ 125% of the recommended dose under same water management yielding 5.95 t ha-1 along with the highest harvest index of 0.58. Results revealed that Pretilachlor at recommended dose might be considered as viable option for weed management in transplanted Boro rice cultivation for effective weed management and satisfactory grain yield provided that appropriate water management is adopted. Journal of Science Foundation 2014;12(2):39-46 DOI: http://dx.doi.org/10.3329/jsf.v12i2.27737